The Impact of Philosophy on Religious Education for High School Students - Bolo, Andreas Doweng; Simanjuntak, Mardohar Batu Bornok; Mahatma, Masmuni (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2022)
This article is a result of a research conducted to examine the interrelation between religion and philosophy and to measure how such interaction is embodied in religious subjects taught in middle-high schools in Indonesia. This is considered important because in Indonesian national education, the religious dimension is regarded fundamental and therefore must be emphasised. The classes are divided based on the students’ religion. In order to prevent such division becomes religious segregation that could lead to practices of intolerance, philosophy is proposed as a rational solution to bridge the discrepancy. This is considered imperative so that in school religion is not understood as an exclusive set of doctrines, but as a subject in education process that brings inclusive and pluralistic attitudes. Three basic and important characteristics are analysed in this article, that is, the breadth of perspective about God, the openness towards other religions, and the willingness to embrace science in general.